Dynamics of Automatic Firing System TypeGas-Operated Weapon - Phon D. NGUYEN (Wojskowa Akademia Techniczna, 2023)
The paper presents a new approach to establish a mathematical model of an automatic firing system of gas-operated weapons, which is based on the Lagrange's theory. In contrast to previous studies, a dynamic model is supplemented with dynamic link between a basic mechanism and a receiver assembly with longitudinal clearance without taking into account horizontal clearance. The automatic firing system of the PKMS machine gun has been selected for calculation of a theoretical model and a verification test. Through comparison between theoretical and experimental results, the mathematical model is proven to be accurate and reliable. The results obtained from the paper are the basis for evaluating the automatic firing system ability to work. This is also a reliable source of reference for designers in the process of optimising the structure of the automatic firing system.
Keywords: Dynamika broni strzeleckiej